Investigation and quantification of food waste generated at USMKK cafeterias - Daud, Rafidah Md (Pusat Pengajian Sains Kesihatan, 2014)
This study aims to investigate and quantify the food waste generated at USMKK cafeterias. This research sampling has been conducted at Nurani, Murni and PPSK cafeterias. The weighing methods were carried out daily and repeated for different cafeteria within five weeks using portable hanging weight scales. A survey was conducted using self-administered questionnaire which was distributed randomly among 369 respondents who are the customers at the USMKK cafeterias. This survey was conducted to investigate the opinions of the research participants on food waste issues within USMKK cafeterias. Semi-structured interview was conducted among cafeteria staffs as to investigate the attitude and behaviour of them in reducing the food waste. The number of customers at the cafeteria was determined using checklist. The results of this study indicated that USMKK cafeterias generates average amount of avoidable food waste with 71.78 kg and unavoidable food waste with 275.93 kg. The regression results (p>0.05) also showed that number of customers is not a significant predictor factors for food wastes generated. From the Kruskall Wallis analysis, there was a difference in the quantity of food wastes generated at USMKK cafeterias (p=0.001). Furthermore, the significant differences (p=0.001) were found between avoidable and unavoidable food wastes quantities generated at Nurani, Murni and PPSK cafeteria as a result of the Mann-Whitney test analysis. According to the research, the predictor of food waste generation is unknown. The attributes influencing food to be wasted at USMKK cafeterias might due to other causes. Findings include a list of determinants that influence customers considered in determining their choice of cafeteria (e.g. location of cafeteria, cheap, food quality). Awareness campaign could increase the level of knowledge about food waste among customers. In addition, it would help the top management to plan suitable programme in minimizing the production of food waste as to support sustainable environment.